Movimentos sociais, reforma agrária e escolaridade: o caso dos alunos do projeto Ceta na Bahia - Daltro, Renato Ribeiro (2009)
This study analyzes the educational trajectory of six students which are matriculated in the Professional Secondary Grade School and in the University Course offered by National Program of Agrarian Reform (Pronera), associated with the Movimento dos Trabalhadores Rurais Assentados, Acampados e Quilombolas (Ceta) and the University of State of Bahia (Uneb). The purpose of this research was to identify what dispositions were assimilated by the students and, consequently, to analyze the relations among their attitude and the earned knowledge and their compromise with Ceta of returning to the camps. The analysis of scholar trajectory is founded on interviews with the students matriculated in the courses of Sustainable Agriculture and Land Pedagogy. The interviews were distributed in groups according to social and economic reality of the students families and then analyzed. In the first moment it was obtained information about the Agrarian Reform on Brazil and the identification of Ceta s Movement on the Regional do Médio São Francisco, where the interviewed students live. The research describes this student s scholar trajectory from the beginning of education process, when they were taught to read and write, to the end of Middle School and the University Study and their expectation about the future. This research is based on the studies of Pierre Bourdieu and his coworkers, who explained the mechanism of strategies of social and cultural reproduction in some social structures, where groups or social classes fight against each other for cultural capital in order to grant reproduction and survival for their progeny or social group. Other studies in the same direction affirm that in situations where the economic conditions are unfavorable to education process, other aspects, mainly the non-scholar aspects, can be identified as successful if it is considered the social environment, the familiar mobilization and the kind of social and scholar trajectory, among other factors. Consequently it was examined this students trajectory, based on their testimonials, analyzing their families cultural capital, social capital and economic capital, their cultivated habitus in the inner of families, their relationship with the Ceta s Movement, the restructuring of their practices and cultural patrimony along the course. The main purpose of this study could be summarized as describing the scholar trajectory of six students, who were raised on popular sectors of open country, who are living a reality replete of subjective expectations of scholar success, in spite of objective possibilities of interruptions and of been repentant in school. Besides, there is a conflict in the inner of mobilization of social movements, where it is fought for ascending or descending positions on the exigency and collective efforts to the access to resources of Agrarian Reform, especially from National Program of Agrarian Reform (Pronera), for a gratuitous and great quality public open country education.